2002
DOI: 10.1002/cncr.10791
|View full text |Cite
|
Sign up to set email alerts
|

Hormone replacement therapy and breast carcinoma risk in Hispanic and non‐Hispanic women

Abstract: BACKGROUNDHormone replacement therapy (HRT) alleviates menopausal symptoms and prevents osteoporosis, but there is concern that long‐term use may have an adverse impact on breast carcinoma risk. Epidemiologic studies report inconsistent findings regarding the relationship between HRT and postmenopausal breast carcinoma risk and there is little information on the HRT‐associated risk among minority women.METHODSTo investigate the effects of HRT on breast carcinoma risk among Hispanic women, we examined data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…This is in agreement with evidence from some studies, [2][3][4]11,14,[33][34][35] but not with others that found a moderate increase in breast cancer risk with ET preparations. 5,10,13,21,[36][37][38][39] We found a moderate elevated risk in users of oral and transdermal estradiol, which is in agreement with results from Lyytinen et al 40 in Finland that found a similar increased risk of breast cancer for oral and transdermal users of estradiol. Use of vaginal estradiol is relatively common compared with oral and transdermal use.…”
Section: Discussionsupporting
confidence: 92%
“…This is in agreement with evidence from some studies, [2][3][4]11,14,[33][34][35] but not with others that found a moderate increase in breast cancer risk with ET preparations. 5,10,13,21,[36][37][38][39] We found a moderate elevated risk in users of oral and transdermal estradiol, which is in agreement with results from Lyytinen et al 40 in Finland that found a similar increased risk of breast cancer for oral and transdermal users of estradiol. Use of vaginal estradiol is relatively common compared with oral and transdermal use.…”
Section: Discussionsupporting
confidence: 92%
“…[13][14][15][16] Women diagnosed with a new primary breast cancer were ascertained through the New Mexico Tumor Registry (NMTR), a member of the Surveillance, Epidemiology and End Results (SEER) Program of the National Cancer Institute. Women diagnosed with invasive or in situ breast carcinoma from January 1, 1992, through December 31,1994, who were residents of the state and between 20 and 80 years of age at diagnosis, were eligible for the study.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 22 studies were identified for possible inclusion (Persson et al, 1996(Persson et al, , 1997Magnusson et al, 1999;Li et al, 2000Li et al, , 2002Li et al, , 2003Moorman et al, 2000;Rockhill et al, 2000;Ross et al, 2000;Schairer et al, 2000;Chen et al, 2002;Daling et al, 2002;Kirsh and Kreiger, 2002;Newcomb et al, 2002;Newcomer et al, 2003;Porch et al, 2002;Ursin et al, 2002;Weiss et al, 2002;Chlebowski et al, 2003;Jernstrom et al, 2003;Million Women Study, 2003;Olsson et al, 2003;Stahlberg et al, 2004). As age at menopause is a critical factor in assessing HT use and breast cancer risk (Pike et al, 1998), we excluded those studies that did not adjust for age at menopause: this criterion excluded five studies (Persson et al, 1997;Moorman et al, 2000;Chen et al, 2002;Li et al, 2002Li et al, , 2003. We also excluded three studies that did not have information on risk by duration of EPT use (Persson et al, 1996;Li et al, 2000;Newcomer et al, 2003), and the study of Olsson et al (2003) for reasons described in the Discussion section below.…”
Section: Methodsmentioning
confidence: 99%